Les déchets post-catastrophe à Haïti : les jeux d’acteurs d’une gestion informelle - Mathieu Durand; Roxana Popescu; Robert D’Ercole (VertigO, 2015)
Post-disaster waste management studies are new in scientist literature as for operational crisis management actors. However, this activity appears to be essential to the immediate response to the crisis (clearing tracks, pipes, etc.), as the phase of recovery and reconstruction. Post-disaster waste Management can help to stimulate local economy and to engage in economic recovery, while providing secondary materials for reconstruction and everyday life. These observations are the result of a cross analysis between international feedback on the waste produced by disasters and fieldwork in Port -au- Prince after the earthquake of 2010. It’s possible to study waste management actors, the skills and the means employed by everyone from the international community to small informal recycler, to companies or governments. Indeed, it is this diversity of actors which characterizes the management of post-disaster waste. The weakness of the Haitian public action has left a huge space for international assistance, stirring colossal budgets. However, we note that more than half of the waste was supported by civil society and the informal recycling and construction sector. This contrast between the ambitions of the United Nations and the reality of local and informal management of post-disaster waste will be analyzing this article.